Decline in mitochondrial bioenergetics and shift to ketogenic profile in brain during reproductive senescence - Yao, Jia; Hamilton, Ryan T.; Cadenas, Enrique; Brinton, Roberta Diaz (Biochimica et biophysica acta, 2010)
We have previously demonstrated that mitochondrial bioenergetic deficits precede Alzheimer's pathology in the female triple transgenic Alzheimer's (3xTgAD) mouse model. Herein, we sought to determine the impact of reproductive senescence on mitochondrial function in the normal non-transgenic (nonTg) and 3xTgAD female mouse model of AD. Both nonTg and 3xTgAD female mice at 3, 6, 9, and 12 months of age were sacrificed and mitochondrial bioenergetic profile as well as oxidative stress markers were analyzed. In both nonTg and 3xTgAD mice, reproductive senescence paralleled a significant decline in PDH, and Complex IV cytochrome c oxidase activity and mitochondrial respiration. During the reproductive senescence transition, both nonTg and 3xTgAD mice exhibited greater individual variability in bioenergetic parameters suggestive of divergent bioenergetic phenotypes. Following transition through reproductive senescence, enzymes required for long-chain fatty acid (HADHA) and ketone body (SCOT) metabolism were significantly increased and variability in cytochrome c oxidase (Complex IV) collapsed to cluster at a approximately 40% decline in both the nonTg and 3xTgAD brain which was indicative of alternative fuel generation with concomitant decline in ATP generation. These data indicate that reproductive senescence in the normal nonTg female brain parallels the shift to ketogenic/fatty acid substrate phenotype with concomitant decline in mitochondrial function and exacerbation of bioenergetic deficits in the 3xTgAD brain. These findings provide a plausible mechanism for increased life-time risk of AD in postmenopausal women and suggest an optimal window of opportunity to prevent or delay decline in bioenergetics during reproductive senescence.